Thermoelectric properties of SnSe nanoribbons: a theoretical aspect. (18th March 2016) - Tyagi, Kriti; Waters, Kevin; Wang, Gaoxue; Gahtori, Bhasker; Haranath, D; Pandey, Ravindra
Abstract: Bulk SnSe is reported to be an excellent thermoelectric material at high temperatures. We now present the results on thermoelectric properties of nanoribbons of SnSe of variable widths obtained using density functional theory coupled with semi-classical Boltzmann theory. The calculated results find armchair nanoribbons of width ≤47 Å to be semiconducting and zigzag nanoribbons of width ≤52 Å to be metallic. A relatively high Seebeck coefficient (≈1720 μ V K −1 ) and low thermal conductivity was calculated for the armchair nanoribbon of 6 Å width, while a large relaxation time and small effective mass was obtained for the armchair nanoribbon of 47 Å width. The calculated results suggest that patterning SnSe into nanoribbons may provide thermoelectric performance that is similar to the monolayer and low-temperature bulk phases of SnSe.